ChemInform Abstract: Preparation of Heteroaryl Ethers from Azine N‐Oxides and Alcohols. Issue 31 (14th July 2016) - Lian, Yajing; Coffey, Steven B.; Li, Qifang; Londregan, Allyn T.
Abstract: In the presence of PyBroP, a broad spectrum of the required heteroaryl ethers can be prepared.